Synchronous Artificial Urinary Sphincter and Inflatable Penile Prosthesis Implantation: Short-Term Outcomes from a Statewide Claims Database. Issue 5 (25th September 2021) - Sweigert, Sarah E.; Chuang, Eric; Patel, Parth M.; Kirshenbaum, Eric; Nelson, Marc; Bajic, Petar; McVary, Kevin T.; Farooq, Ahmer; Gonzalez, Christopher
Abstract: Purpose: The 2 most common adverse effects of radical prostatectomy are erectile dysfunction and stress urinary incontinence which often require surgical management with penile prosthesis (PP) and artificial urinary sphincter (AUS) implantation, respectively. There are conflicting reports regarding whether these procedures should be combined into 1 surgical setting or staged. We sought to evaluate the safety of performing these procedures in the same operative setting. Materials and Methods: We performed a retrospective analysis using the Healthcare Cost and Utilization (HCUP) State Inpatient Database (SID) and State Ambulatory Surgery Database (SASD) for the states of California (2007–2011) and Florida (2009–2014). ICD-9-CM diagnosis and CPT codes were used to identify adult males who underwent both PP and AUS implantation and outcomes regarding readmissions, emergency room (ER) presentations, and complications were reviewed. Results: Patients undergoing synchronous PP-AUS implantation had significantly higher 90-day readmission rates (13.9% vs 7.2%, p <0.001), suffered higher rates of device complications (6.1% vs 3.4%, p=0.021), and were more likely to have minor complications (8.89% vs 2.35%, p <0.001) compared to nonsynchronous device placement. No differences in major complications or 90-day ER visits were observed. Conclusions: Synchronous PP and AUS implantation is feasible but may be associated with higher readmission rates, device complications and postoperative complications compared to a staged approach. This further validates findings from prior studies.